Mediating Effects of Earnings after Tax: Cost of Good Sold, Sales Growth, and Dividend Payout Ratio - Gina Sakinah; Ponirah, Ade; Iwan Setiawan; Awang Dody Kardeli; Izzul Haq Firman Maulana (Tazkia Islamic University College, 2024)
The research aims to analyze the mediating effect of Earning After Tax on the influence of Cost of Good Sold (COGS) and Sales Growth on the Dividend Payout Ratio (DPR). This research uses a descriptive verification method with a quantitative approach. The research method uses classical assumption, associative, and path analyses. The analysis in this research is supported by the use of SPSS for Windows version 23. The data is secondary data from the Indonesian Stock Exchange website (www.idx.co.id). Based on the research results, it was concluded that there is a significant influence between the Cost of Good Sold (COGS) on the Dividend Payout Ratio (DPR) in consumer goods industry companies listed on the Jakarta Islamic Index (JII) for the 2011-2019 period with the results t count > t table (2.075 > 2.042) so Ha is accepted. There is an insignificant influence between Sales Growth on the Dividend Payout Ratio (DPR) in consumer good industry companies listed on the Jakarta Islamic Index (JII) for the 2011-2019 period because t count < t table (1.458 < 2.042), so Ho is accepted. There is a significant influence between Earning After Tax (EAT) and the Dividend Payout Ratio (DPR) in consumer goods industry companies listed on the Jakarta Islamic Index (JII) for the 2011-2019 period. Ha is accepted with the results t count > t table (4.237 > 2.042). Meanwhile, the Cost of Good Sold (COGS) influences the Dividend Payout Ratio (DPR) through Earning After Tax (EAT) Z value (2.702) and p-value 0.006 < 0.050. Moreover, Sales Growth influences the Dividend Payout Ratio (DPR) through Earning After Tax (EAT) Z value (2.178) and p-value 0.0296 < 0.050.